Investigation on the Generation and Evolution Characteristics of Vortex as Liquid Film Flows on Uneven Walls. Issue 4 (March 2019) - Liu, Mei; Zhen, Meng; Liang, Xiujun; Wu, Zhengren
Abstract: Based on Fluent numerical simulation software, a numerical model of vapor-liquid two-phase liquid film flow on inclined non-planar wall was established by VOF method. The three-dimensional liquid film flow of the corrugated wall was simulated and analyzed. The results show that the degree of volatility is a key factor affecting eddy current characteristics. Keeping the wavelength of the corrugated structure constant, when m = 0.0313, m = 0.0417, no vortex structure is generated. As the waveform increases, a diversion occurs and eddy currents are generated. m = 0.125, m = 0.1667, the eddy current size increases, and the shape becomes irregular. Taking the wall surface α of the corrugated structure as the research object, the larger the vortex in the corrugated structure, the larger the maximum velocity in the liquid film. Therefore, the existence of the amount of vorticity inside the wall structure can't be ignored for the effect of drag reduction.